2011
DOI: 10.1177/0885328210390542
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic and Traditional Albumin Isotherms on Cellulose: A Model for Wound Protein Adsorption on Modified Cotton

Abstract: Albumin is the most abundant protein found in healing wounds. Traditional and chromatographic protein isotherms of albumin binding on modified cotton fibers are useful in understanding albumin binding to cellulose wound dressings. An important consideration in the design of cellulosic wound dressings is adsorption and accumulation of proteins like albumin at the solid-liquid interface of the biological fluid and wound dressing fiber. To better understand the effect of fiber charge and molecular modifications i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
3
0
1
Order By: Relevance
“…30,31 In addition, we and others have shown that albumin, which is the protein of highest concentration in wounds, does not unfold on cellulosic materials. 32,33 The hydrophilic material and surface charge derives from an abundance of hydroxyl functionality present in the nanocellulose structure. As discussed above, the ability to combine measurable protease detection with a dressing motif that neutralizes the effect of proteases is one of the specific goals of wound-healing biomaterial design.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 In addition, we and others have shown that albumin, which is the protein of highest concentration in wounds, does not unfold on cellulosic materials. 32,33 The hydrophilic material and surface charge derives from an abundance of hydroxyl functionality present in the nanocellulose structure. As discussed above, the ability to combine measurable protease detection with a dressing motif that neutralizes the effect of proteases is one of the specific goals of wound-healing biomaterial design.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to proteins, cellulose polymers are relatively non-immunogenic [ 107 , 108 ]. In addition, it has been shown that albumin, which is the protein of highest concentration in wounds, does not unfold on cellulosic materials [ 109 , 110 , 111 ]. However, the human body lacks enzymes necessary to completely breakdown of cellulose materials, however through chemical modification it is possible to augment the biodegradation [ 103 ].…”
Section: Modified Cellulose Productsmentioning
confidence: 99%
“…Among these bio-based polymers are cellulose and its esters and ethers (Klemm et al, 2005; Arca et al, 2018). Many authors therefore investigated the interaction of proteins with surfaces of polymers and elucidated its relation to hydrophilicity (Fujimori et al, 1998; Alves et al, 2010), charge (Edwards et al, 2012), morphology or solvation (Lu et al, 2007). Such studies were also conducted for cellulose and surface modified materials composed of it (Solin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%